Influenza vaccine effect on risk of stroke occurrence: a systematic review and meta-analysis - Zahhar, Jalal A.; Salamatullah, Hassan K.; Almutairi, Maher B.; Faidah, Dania E.; Afif, Lena M.; Banjar, Toka A.; Alansari, Nayef; Betar, Manar; Alghamdi, Saeed; Makkawi, Seraj (Frontiers in Neurology, 2024)
Background Stroke is a significant global cause of mortality and long-term disability, potentially influenced by infections that heighten systemic inflammation and thrombotic events. The full impact of influenza vaccination on stroke remains uncertain. This systematic review and meta-analysis aimed to investigate the association between influenza immunization and stroke incidence. Methods We searched for randomized controlled trials (RCTs), case–control, and cohort studies published in PubMed/Medline, Cochrane-Central-Register-of-Controlled-Trials (CENTRAL), and Embase until 5 December 2022, and identified articles investigating the effect of influenza vaccine on stroke occurrence. All articles were screened by two independent reviewers. We performed a meta-analysis to investigate the risk of stroke occurrence in vaccinated vs. unvaccinated individuals. The random-effects model was used in all statistical analyses. Results Among the 26 articles meeting our criteria, 10 were retrospective cohort studies, 9 were case–control studies, 3 were prospective cohort studies, 3 were RCTs and 1 case-series. Overall, the studies showed a significant decrease in the risk of stroke incidence/hospitalization among vaccinated patients (OR = 0.81, 95% CI [0.77–0.86], p = 0.00001). Furthermore, studies showed flu vaccine decreases the occurrence of mortality among stroke patients (OR = 0.50, 95% CI [0.37–0.68], p = 0.00001). Sub-group analysis revealed significant protective effect for patients with specific comorbidities including atrial fibrillation (OR = 0.68, 95% CI [0.57–0.81], p = 0.0001), diabetes (OR = 0.76, 95% CI [0.66–0.87], p = 0.0001), Chronic obstructive pulmonary disease (OR = 0.70, 95% CI [0.61–0.81], p = 0.00001), and hypertension (OR = 0.76, 95% CI [0.70–83], p = 0.00001). Conclusion The current meta-analysis further supports prior findings that influenza vaccination reduces stroke risk, particularly in patients with comorbidities. Guidelines should promote vaccination for at-risk individuals.